PEMETAAN AYAT-AYAT NĀSIKH-MANSŪKH (Studi Komparatif dalam kitab Al- Burhan Fi Ulumul Quran dan Al-Itqān Fi Ulumul Quran) - Anggun Murniati; Ahmad Munir (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2025)
This article compares the concept of nāsikh–mansūkh in two classical works of Qur’anic sciences: Al-Itqān by al-Suyūṭī and Al-Burhān by az-Zarkashī. Using a textual comparative method, it examines their definitions, criteria, and classification of surahs containing abrogating or abrogated verses. Although both scholars agree that abrogation applies only to legal verses, their mappings differ due to methodological variations. Al-Suyūṭī identifies 43 surahs as free from abrogation, while az-Zarkashī lists only 34, applying a stricter interpretation of verses that remain recited but are no longer practiced. These differences reflect diverse scholarly perspectives rather than contradiction. The study recommends integrating both approaches to develop a more comprehensive understanding of nāsikh–mansūkh.